2019
DOI: 10.1093/ecco-jcc/jjz188
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioids induce Gut Dysbiosis and Exacerbate Colitis in a Murine Model of Inflammatory Bowel Disease

Abstract: Abstract Background and Aims Opioids are the most prescribed analgesics for pain in inflammatory bowel diseases [IBD]; however, the consequences of opioid use on IBD severity are not well defined. This is the first study investigating consequences of hydromorphone in both dextran sodium sulphate [DSS]-induced colitis and spontaneous colitis (IL-10 knockout [IL-10-/-]) mouse models of IBD. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 61 publications
4
32
0
Order By: Relevance
“…Recent studies have, therefore, investigated how the interactions between gut microbiota and the immune system influence the development of IBD. It is proposed that a compromised mucosal immune function, including an increase in intestinal permeability or epithelial cell injury, may enable an abnormally high concentration of pathogens to be transmitted to underlying lamina propria, consequently triggering a persistent inflammation response in genetically susceptible individuals [ 107 ].…”
Section: Intestinal Microbiota and Ibdmentioning
confidence: 99%
“…Recent studies have, therefore, investigated how the interactions between gut microbiota and the immune system influence the development of IBD. It is proposed that a compromised mucosal immune function, including an increase in intestinal permeability or epithelial cell injury, may enable an abnormally high concentration of pathogens to be transmitted to underlying lamina propria, consequently triggering a persistent inflammation response in genetically susceptible individuals [ 107 ].…”
Section: Intestinal Microbiota and Ibdmentioning
confidence: 99%
“…Our earlier study has shown that morphine could exaggerate DSS-induced mucosal inflammation syndrome 15 . As shown in Figure 7 , the EVs that are derived from intestinal organoid, rather than morphine-treated organoid, could efficiently alleviate colitis.…”
Section: Resultsmentioning
confidence: 93%
“…Regarding opioid-induced dysbiosis, to date, most of the data originate from preclinical studies, in which mice were exposed to morphine for different time periods [128,129,131,[133][134][135]. However, in some experiments, other opioid agents were used, such as loperamide [136,137] or hydromorphone [138], and there are some common patterns in the microbial composition of animals irrespective of the type of opioid used, allowing to draw some general conclusions on the effect of opioids on microbiota. Moreover, some of these changes have also been observed in non-human primates [139], as well as in opioid user cirrhotic patients compared to those not on opioids [140], or in heroin addicts [141], further supporting the complexity and translational relevance of the results.…”
Section: The Role Of Mors In the Gut Microbiota: Dysbiosis Opioid Tolerancementioning
confidence: 99%
“…Hence, opioid-induced microbial alterations can generate a pro-inflammatory milieu, which can compromise the gut epithelial barrier and allow luminal aggressive factors (bacteria, bile acids) to penetrate into the gut wall and trigger an immune response, further amplifying the initial inflammation. Gut inflammation in response to opioid administration is typically characterized by enhanced intestinal permeability, the activation of Toll-like receptor-2 (TLR-2), TLR-4, and elevated levels of various pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-6, IL-17) in the intestine, mesenteric lymph nodes, and remote organs [128,133,134,138].…”
Section: The Role Of Mors In the Gut Microbiota: Dysbiosis Opioid Tolerancementioning
confidence: 99%
See 1 more Smart Citation